Integrating Islamic Boarding School Values into Indonesian Language Learning - Ahmad Faizi; Eko Hardinanto; Alfian Setya Nugraha; Arisni Kholifatu As; Icha Fadhilasari (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study examines how Nahdlatul Ulama (NU) values moderation (tawasuth), balance (tawazun), and tolerance (tasamuh) are integrated into Indonesian language learning in pesantren-based high schools in Jombang, Indonesia. Using a qualitative ethnopedagogical approach, data were gathered through observation, interviews, and document analysis involving 20 purposively selected teachers and students. The findings show that learning practices in these schools reflect the principles of Culturally Responsive Teaching (CRT) rooted in NU’s Islamic traditions. Moderation appears in educational sanctions that balance academic discipline and moral guidance, while tolerance emerges through heterogeneous student groupings that foster empathy and intercultural communication. These practices demonstrate how NU’s moral-spiritual values shape classroom management, learning materials, and teacher–student interactions. The study introduces the concept of Islamic Culturally Responsive Pedagogy, expanding CRT theory by embedding Islamic ethnopedagogical principles that emphasize spiritual and social harmony. Theoretically, this research contributes to the development of culturally grounded learning models that integrate local religious values. In practice, the findings offer guidance for designing character-based, inclusive Indonesian language learning suitable for pesantren-based schools and other multicultural educational settings.